(3GdJWhQGJ GdYGdejI hGfYcGSGJgG Ydi CYeGd GdHfhc (B/s - (3MeGO, WGQb YHO GdYGds ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 1999)
(3GdJWhQGJ GdYGdejI hGfYcGSGJgG Ydi CYeGd GdHfhc, Jbjje COGA GdHfhc GdJLGQjI (B((3JMdjd GdYGFO hGdeNGWQI(B)(3, GfOeGL hNUNUI GdHfhc, JbOjQ bjeI GdHfc dCZQGV GdGfOeGL Ch GdNUNUI, GdGHJcGQGJ GdeGdjI (B((3GdeaGgje, GdGOGQI GdeMGSHI(B).s
(3GdeQGLY U(B.237s
Keywords: (3GdHfhc(B- (3eMGSHIs; (3LfhH TQbj BSjG(B- (3GdCMhGd GdEbJUGOjIs